2017
DOI: 10.1002/jssc.201601059
|View full text |Cite
|
Sign up to set email alerts
|

New application of chitosan‐grafted polyaniline in dispersive solid‐phase extraction for the separation and determination of phthalate esters in milk using high‐performance liquid chromatography

Abstract: Chitosan-grafted polyaniline was synthesized and applied as a sorbent for the preconcentration of phthalate esters in dispersive solid-phase extraction. By coupling dispersive solid-phase extraction with high-performance liquid chromatography and response surface methodology (central composite design), a reliable, sensitive, and cost-effective method for simultaneous determination of phthalate esters including dimethyl phthalate, di-n-butyl phthalate, and di(2-ethylhexyl)phthalate was developed. The morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 44 publications
1
11
1
Order By: Relevance
“…4, it was observed that the removal % of nitrate remained constant throughout the acidic and neutral solutions; however, after pH 6, a decrease from 90 to 60% was observed which implied that the maximum removal % can be achieved by keeping the pH within acidic or neutral range. The remarkably high initial adsorption capability of the reported nanocomposite were due to the presence of the positive surfaces of all three components namely polyaniline, cobalt and magnetite (oxides in general) at acidic pH which sustained the attractive electrostatic interaction between the positive sorbent and the negative nitrate ions [41], [44]. While, the low adsorption efficiency at high pH values, had occurred due to the increasing competition between the coexisting OHand nitrate ions for the active sites of the sorbent [29], [45].…”
Section: Effect Of Phmentioning
confidence: 95%
“…4, it was observed that the removal % of nitrate remained constant throughout the acidic and neutral solutions; however, after pH 6, a decrease from 90 to 60% was observed which implied that the maximum removal % can be achieved by keeping the pH within acidic or neutral range. The remarkably high initial adsorption capability of the reported nanocomposite were due to the presence of the positive surfaces of all three components namely polyaniline, cobalt and magnetite (oxides in general) at acidic pH which sustained the attractive electrostatic interaction between the positive sorbent and the negative nitrate ions [41], [44]. While, the low adsorption efficiency at high pH values, had occurred due to the increasing competition between the coexisting OHand nitrate ions for the active sites of the sorbent [29], [45].…”
Section: Effect Of Phmentioning
confidence: 95%
“…Phthalate esters (PAEs) are one kind of persistent organic pollutants. They are extensively used as plasticizers for polymers such as poly(vinyl chloride), polystyrene (PS), and polyethylene in plastics industries [1,2]. The PAEs At present, common analytical methods of PAEs are based on GC [13], GC-MS [14][15][16], LC [17], LC-MS/MS [18,19], IR or FFTIR spectroscopy [20], fluorescence spectroscopy [9], and ELISA [21].…”
Section: Introductionmentioning
confidence: 99%
“…Phthalate esters (PAEs) are one kind of persistent organic pollutants. They are extensively used as plasticizers for polymers such as poly(vinyl chloride), polystyrene (PS), and polyethylene in plastics industries . The PAEs have caused a wide public concern as endocrine disruptors, which have carcinogenicity and testicular toxicity , and have been shown to affect reproductive organs and fertility .…”
Section: Introductionmentioning
confidence: 99%
“…Quick and effective sample preparation techniques combined with reliable analytical methods are necessary . Sample preparation plays an important part in the research field of phenoxyacetic acids in water analysis, and the commonly used methods include LLE and SPE .…”
Section: Introductionmentioning
confidence: 99%
“…Sample preparation plays an important part in the research field of phenoxyacetic acids in water analysis, and the commonly used methods include LLE and SPE [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%